2010
DOI: 10.1111/j.1755-3768.2009.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of visual impairment in a rural North‐east China adult population: a population‐based survey in Bin County, Harbin

Abstract: ABSTRACT.Purpose: To investigate the prevalence and causes of visual impairment in a rural population in north-east China. Methods: A population-based study was conducted within Bin County, Harbin of north-east China. Low vision and blindness were defined using the World Health Organization categories of visual impairment. The prevalence of visual impairment was estimated, and causes were identified based on best-corrected visual acuity (BCVA) as well as presenting visual acuity (VA). Results: Out of 5764 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
2
17
1
2
Order By: Relevance
“…The high prevalence found in Thailand could be due, in part, to limited access to health care in general for those living in rural areas in developing countries, as well as, a high rate of uncorrected refractive error including presbyopia (Holden, Fricke, Ho, Wong, Schlenther, Cronjé, Burnett, Papas, Naidoo, & Frick, 2008) as is anticipated for this part of the world (Dandona & Dandona, 2006;Holden et al, 2008). A number of findings in the current study differed from those reported in the previous study by LaGrow et al (2011b), but were similar to those reported elsewhere (Chia, Wang, Rochtchina, Smith, Cumming, & Mitchell, 2004;Evans, Fletcher, Wormald, Ng, Stirling, Smeeth, Breeze, Bulpitt, Nunes, Jones, & Tulloch, 2002;Horowitz et al, 2005;Jin & Wong, 2008;LaGrow et al, 2009;Michon, Lau, Chan, & Ellwein, 2002;Nirmalan, Thulasiraj, Maneksha, Rahmathullah, Ramakrishnan, Padmavathi, Munoz, & Ellwein, 2002;Oye & Kuper, 2007;Song, Sun, Shao, Zhou, Kang, Sui, & Yuan, 2010;J. J. Wang, Mitchell, & Smith, 2000;Wong, Chong, Wong, Rosman, Aung, Loo, Shen, Loon, Tan, Tai, & Saw, 2008).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The high prevalence found in Thailand could be due, in part, to limited access to health care in general for those living in rural areas in developing countries, as well as, a high rate of uncorrected refractive error including presbyopia (Holden, Fricke, Ho, Wong, Schlenther, Cronjé, Burnett, Papas, Naidoo, & Frick, 2008) as is anticipated for this part of the world (Dandona & Dandona, 2006;Holden et al, 2008). A number of findings in the current study differed from those reported in the previous study by LaGrow et al (2011b), but were similar to those reported elsewhere (Chia, Wang, Rochtchina, Smith, Cumming, & Mitchell, 2004;Evans, Fletcher, Wormald, Ng, Stirling, Smeeth, Breeze, Bulpitt, Nunes, Jones, & Tulloch, 2002;Horowitz et al, 2005;Jin & Wong, 2008;LaGrow et al, 2009;Michon, Lau, Chan, & Ellwein, 2002;Nirmalan, Thulasiraj, Maneksha, Rahmathullah, Ramakrishnan, Padmavathi, Munoz, & Ellwein, 2002;Oye & Kuper, 2007;Song, Sun, Shao, Zhou, Kang, Sui, & Yuan, 2010;J. J. Wang, Mitchell, & Smith, 2000;Wong, Chong, Wong, Rosman, Aung, Loo, Shen, Loon, Tan, Tai, & Saw, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…J. Wang, Mitchell, & Smith, 2000;Wong, Chong, Wong, Rosman, Aung, Loo, Shen, Loon, Tan, Tai, & Saw, 2008). As in these studies, those who had difficulty with seeing were found to be older (Horowitz et al, 2005;Jin & Wong, 2008), disproportionately female (Evans et al, 2002;Horowitz et al, 2005;Michon et al, 2002;Nirmalan et al, 2002;Oye & Kuper, 2007;Song et al, 2010;Wong et al, 2008), and to have a poorer perception of health (Chia et al, 2004;LaGrow et al, 2009;J. J. Wang et al, 2000) and lower rating of QOL (Bekibele & Gureje, 2008a;LaGrow, Alpass, Stephens, & Towers, 2011a;LaGrow et al, 2011b;Lamoureux, Fenwick, Moore, Klaic, Borschmann, & Hill, 2009;Nutheti, Shamanna, Nirmalan, Keeffe, Krishnaiah, Rao, & Thomas, 2006;Tran, Mahdi, Sivasubramaniam, Gudlavalleti, Gilbert, Shah, Ezelum, Abubakar, & Bankole, 2011;C.…”
Section: Discussionmentioning
confidence: 90%
“…[2,15-16,18-19,21-29] However, the differential impact of sex on visual impairment has been inconsistent in the literature with some studies finding no differences between men and women. [14-15,19,22,25] Among studies where significant sex differences were present, women were more likely to have visual impairment compared to men, [2,16,23-24,27-29] consistent with our results. In the present study, older age was a consistent predictor of increased visual impairment, but the effects were most pronounced in men and varied by racial/ethnic group, suggesting that the demographic characteristics (age, sex, and ethnicity) of the population may interact and result in different prevalence of impairment which, without adequate adjustment, could obfuscate comparisons of prevalence across countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, the result should be carefully interpreted. Eleven surveys performed in East and Central China, including Beijing (n = 2) [6,7], Jiangsu (n = 2) [6,15], Guangdong (n = 2) [6,16], Heilongjiang (n = 2) [6,17], Hebei (n = 2) [6,18], Jiangxi (n = 1) [6],were published in English. Only 1 study, which included 3 surveys in Western China, was published in English [6].…”
Section: Discussionmentioning
confidence: 99%